Application Of Project Based Learning (Pjbl) Model To Improve Students' Biology Learning Outcomes At Sman 2 Taliwang - Masitah, Baiq Siti; Rahmawati, Fitri; Ayu Permatasari, Siska Diah (Lembaga Penelitian dan Pendidikan Mandala, 2025)
The Implementation of the Project Based Learning (PjBL) Model in Improving Student Learning Outcomes in Biology at SMAN 2 Taliwang. Undergraduate thesis, Biology Education Study Program, Faculty of Teacher Training and Education, Cordova University. Supervised by Fitri Rahmawati, S.Pd., M.Pd. as the first advisor, and Siska Diah Ayu Permatasari, S.Pd., M.Pd. as the second advisor.This research aims to investigate the effect of the Project Based Learning (PjBL) model on students' learning outcomes in Biology at SMAN 2 Taliwang. Problems observed in biology learning include low academic achievement, the dominance of lecture methods, and a lack of active student participation. This study used a quantitative approach with a quasi-experimental design in the form of a pretest-posttest control group. The sample consisted of two classes: an experimental class applying the PjBL model and a control class using conventional teaching methods. The instrument used was a learning outcome test that had been validated and proven reliable. Data analysis included normality test, homogeneity test, and two-way ANOVA.The findings showed a significant difference in student learning outcomes between those taught using PjBL and those with conventional learning. The significance value was 0.004 (< 0.05), with a mean gain score difference of 110.767. Therefore, the PjBL model is proven effective in improving students’ cognitive learning outcomes on the topic of viruses.